Association of Autonomic imbalance with Parental history of Type 2 Diabetes Mellitus - Bagudai, Satyajit; Upadhyay, Hari Prasad (Asian Journal of Medical Sciences, 2020)
Background: Off springs with a parental history of type 2 diabetes mellitus are genetically susceptible to develop diabetes. In some recent reports it has been shown that these vulnerable population exhibit altered autonomic activity even before the manifestations of disease. Autonomic dysfunction might be the initial cardiac pathology in subclinical type2 diabetes. Till now very few studies have been done to find out the early outcomes of this genetic transmission. Keeping in view of the above facts, the current study was carried out to find out the association between autonomic dysfunction and parental history of diabetes. Aim and Objectives: This study was aimed to quantify and compare the difference (if any) of heart rate recovery in response to 3minute step test between the young non diabetic children of non-diabetic and diabetic parents. Materials and Methods: Fifty-one non diabetic students were divided into two groups. One group comprised of students with parental history of type2 diabetes mellitus and another group with students without parental history of diabetes. Each student was subjected to 3minute Master step test. Recordings of heart rate were made before and after exercise. Heart arte recovery (HRR) in 1 minute (HRR1) as well as in 2, 3 and 4 minute (HRR2,HRR3, HRR4) were recorded and analyzed. Results: The resting (basal) as well as 1stminute heart rate recovery (HRR1) was not significantly different between the two groups. Likewise, the 2nd minute HRR (HRR2), 3rd minute HRR (HRR3) and 4th minute HRR (HRR4) respectively were also not significantly different between the two groups. Conclusion: This study concludes that there is no difference in the heart rate recovery in response to the exercise stress test between the young non diabetic children of non-diabetic and diabetic parents. Therefore, parental history of diabetes does not have any impact on the cardiovascular autonomic activity before the disease manifestation.